2021
DOI: 10.3390/f12121688
|View full text |Cite
|
Sign up to set email alerts
|

Valuing Recreational Services of the National Forest Parks Using a Tourist Satisfaction Method

Abstract: Estimating the economic value of ecosystem services has become one of the most fertile areas in ecological economics. In this paper, we propose a novel method of using a tourist satisfaction model to evaluate the recreational services being embedded in forest ecosystems. We establish a functional relationship between tourist satisfaction and recreational attributes based on the survey data of China National Forest Parks. The results indicate that each recreational attribute considered enables the generation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…With the three attributes, each with three labels, we applied an experimental design technique of 3 3 combinations for a total of 81 alternatives with main effects, which generated nine orthogonal combinations, which were blocked into three different questionnaire versions, each including three choice sets [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…With the three attributes, each with three labels, we applied an experimental design technique of 3 3 combinations for a total of 81 alternatives with main effects, which generated nine orthogonal combinations, which were blocked into three different questionnaire versions, each including three choice sets [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, environmental education in national parks is conducive to promoting the sustainable development of forest tourism, and in-depth research has been conducted on this issue [25]. Based on the survey data of national parks in China, Kang [26] established a functional relationship between tourist satisfaction and leisure attributes. They found that entertainment attributes can bring a lot of tourism welfare to tourists, while tourism congestion has a negative effect on tourists' satisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When the population density reaches a certain standard and the need for personal space is obstructed for a long period of time, people will feel crowded; thus, we use the term "perceived crowding" to describe this subjective and negative feeling of being constrained under the condition of excessive external stimulation [12]. Crowding is often used as an important evaluative indicator to measure tourists' satisfaction with parks, and a large body of research suggests that crowding can have a potentially negative impact on satisfaction [13]. Put simply, as the number of people increases, satisfaction declines [14].…”
Section: Introductionmentioning
confidence: 99%